The Relationship Between Auditory Learning Strategies and English Achievement of English Education Students - Abdi Aldio Saputra; Sudarman; Rani Herning Puspita; Yeni Rahmawati (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
Listening is a fundamental skill in English Education programs, as it enables students to understand lectures, follow instructions, and participate effectively in academic discussions. However, many students still experience difficulties in achieving satisfactory listening performance, which may be related to how they apply learning strategies during listening activities. Among various learning strategies, auditory learning strategies are particularly relevant because they emphasize learning through spoken input. This study aimed to examine the application of auditory learning strategies and their relationship with English listening achievement among English Education students. A quantitative correlational design was employed, involving 63 students from Universitas Muhammadiyah Kalimantan Timur. Data on auditory learning strategies were collected using a questionnaire with a four-point Likert scale, while listening achievement data were obtained from students’ official listening course scores. Descriptive statistics and Pearson Product–Moment correlation analysis were used for data analysis. The findings indicate that students actively apply auditory learning strategies across several strategy categories, with specific items achieving the highest total points in each section. The results also reveal a very strong and statistically significant positive relationship between auditory learning strategies and English listening achievement. These findings suggest that consistent engagement in auditory learning strategies is closely associated with better listening achievement in academic contexts.